Encoding of action by the Purkinje cells of the cerebellum - Herzfeld, David J. (Nature, 2015)
Execution of accurate eye movements depends critically on the cerebellum(1,2,3), suggesting that Purkinje cells (P-cells) may predict motion of the eye. Yet, this encoding has remained a long-standing puzzle: P-cells show little consistent modulation with respect to saccade amplitude(4,5) or direction(4), and critically, their discharge lasts longer than duration of a saccade(6,7). Here, we analyzed P-cell discharge in the oculomotor vermis of behaving monkeys(8,9) and found neurons that increased or decreased their activity during saccades. We estimated the combined effect of these two populations via their projections on the caudal fastigial nucleus (cFN) and uncovered a simple-spike population response that precisely predicted the real-time motion of the eye. When we organized the P-cells according to each cell's complex-spike directional tuning, the simple-spike population response predicted both the real-time speed and direction of saccade multiplicatively via a gain-field. This suggests that the cerebellum predicts the real-time motion of the eye during saccades via the combined inputs of P-cells onto individual nucleus neurons. A gain-field encoding of simple spikes emerges if the P-cells that project onto a nucleus neuron are not selected at random, but share a common complex-spike property.